A New Perspective on English Coursebooks: High School Students' Evaluations in the Turkish Context - Çoban, Zelal; Selvi, Batuhan (Afyon Kocatepe University, 2026)
The fundamental aim of this study is to demonstrate a group of high school students’ point of view from different grades with regards to English textbooks prepared by Ministry of National Education by means of different data collection tools. The study was conducted with converged design which belongs to mixed method research. while a four-point Likert scale ranging from strongly disagree (1) to strongly agree (4) was applied for the quantitative part, the qualitative phase was implemented with semi-structured interview questions. Topic variety was found moderately suitable. In addition, cultural representations were evaluated as restricted mainly on British and American culture. Language skills development was viewed as average, with reading and listening receiving relatively higher scores. Grammar explanation lacked clarity and vocabulary teaching methods were considered moderately effective. These findings suggest that coursebook developers should enhance content engagement, cultural inclusivity and interactive activity design to better address students’ learning needs. Furthermore, the results of the study indicated students’ can also evaluate and make judgements about their English coursebooks.

Bu çalışmanın başlıca amacı, farklı veri toplama araçları kullanarak devlet okulunda okuyan farklı kademelerdeki lise öğrencilerinin Milli Eğitim Bakanlığı tarafından hazırlanan İngilizce ders kitaplarına ilişkin düşüncelerini açığa çıkartmaktır. Bu çalışma, karma araştırma yöntemi deseni olan yakınsayan paralel desenle yürütülmüştür. Nicel kısım için Likert ölçeği kullanılırken nitel kısım için yarı yapılandırılmış görüşme sorularına başvurulmuştur. Ders kitabındaki konu çeşitliliği, kısmen uygun bulunmuştur. Ayrıca kitabın kültürel yönden daha kapsayıcı olması gerektiği ve daha çok İngiliz ve Amerikan kültürünü barındırdığı öğrenciler tarafından vurgulandı. Dil becerileri ortalama görülürken okuma ve dinlemeye daha çok vurgu yapıldığı açığa çıkarıldı. Dil bilgisi açıklamaları yetersiz bulundu ve kelime öğretim yöntemleri kısmen etkili olarak değerlendirildi. Bulgular, ders kitabı yazarlarının kitaptaki içeriğin ilgi çekiciliğini, kültürel kapsayıcılığını ve interaktifliğini öğrencilerin öğrenme ihtiyaçlarını karşılamak için arttırması gerektiğinin altını çiziyor. Buna ilaveten araştırmanın sonuçları, öğrencilerin de İngilizce ders kitabı hakkında değerlendirme yapabilip bir yargıya ulaşabileceklerini gösterdi.
İngilizce Ders Kitaplarına Yeni Bir Bakış Açısı: Türkiye Bağlamında Lise Öğrencilerinin Düşünceleri
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)